Alleged Violation of Article 35 Paragraph (1) of Law Number 20 of 2008 Regarding the Implementation of the Partnership between PT Bulungan Citra Agro Persada (PT Bcap) and the Multi-Business Cooperative Mega Buana Decision: 21/KPPU-K/2019 - Priyanto, Eka; Mardiansah, Songgi; Respati, Gilang; Irawan, Feri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The partnership between PT BCAP and KSU Mega Buana is an example of collaboration between a large company and a cooperative that has the potential to provide benefits for both parties. This partnership is expected to increase the income and welfare of cooperative members, as well as expand the market reach of the company's products and services. However, there are several things that need to be considered in implementing this partnership to ensure that the partnership is carried out fairly and in accordance with applicable regulations. These things include fair distribution of profits, preventing abuse of dominant position, fulfilling obligations, and monitoring and evaluation. This research aims to analyze the mechanism for implementing the partnership between PT BCAP and KSU Mega Buana, including the division of work, resource allocation, and policies implemented. This research also aims to identify indications or concrete evidence that shows violations of Article 35 Paragraph (1) of Law Number 20 of 2008 in the implementation of this partnership